Peran BI’AH ‘Arabiyah Dalam Meningkatkan Keterampilan Berbahasa Aarab Mahasiswa Program Studi Manajemen Dakwah PadaFakultas Dakwah dan Komunikasi UIN Raden Fatah Palembang - M.amin Sihabuddin (Wardah, 2019)
Abstract: Background research is an Arabic language environment to realize Arabic language skills especially for da'wah management study program students. The language environment is said to be very important because it has a very large function and role, especially for students to compete in the world applying for jobs. Therefore, through the research the author wants to look deeper and find out how the role of the Arabic language environment exists in the da'wah management study program and the extent of its role in improving students' Arabic language skills. The method in this study uses quantitative research with a sample of 52 students. The results of research conducted on 52 da'wah management study program students at the Da'wah and Communication Faculty of Raden Fatah State Islamic University Palembang showed that 78.53% of students were able to improve their Arabic speaking skills with the existing language environment on campus. Keywords: Arabic language environment, Arabic language skills